Development and Sensory Evaluation of Dates Ice Cream - Wan Sulaiman, Wan Nor Hafiza; Ibrahim, Alif Amsyar; Halim, Nor Adlina; Sulaiman, Nur Amirah Syafiqah; Mohd Nor, Muhammad I’zzat (Multidisciplinary Applied Research and Innovation, 2022)
Ice cream is the most consumed dairy product in the world because it contains nutrients that provide the body energy. However, some people may have problems with ice cream since it is dairy-based and contains lactose, a milk sugar. Therefore, low-calorie ice cream is highly in demand since sugar, which is used to produce ice cream, has a high calorie density. While, dates are an organic food with high nutritional value that are rich in fibre, protein, carbohydrates, sugars, vitamins, minerals, and substantial amounts of natural antioxidants. Dates are a possibility for improving the nutritional content of food products because of their advantages. The development and consumption of healthy ingredients are currently quite popular due to the growing public awareness of the relationship between nutrition and wellness. Observing the potential and benefits, this study was conducted to formulate a new ice cream with dates taste and study the sensory analysis, as well as to evaluate the nutritional facts of dates ice cream. Dates Ice Cream was developed as a method of reducing the risk of increasing childhood obesity. The research methodology involved organoleptic examination of taste, texture, smell, colour and overall acceptability. A number of 40 respondents were selected randomly. The hedonic scale of five points was applied in this research and descriptive analysis was performed to examine the data obtained using SPSS. According to the findings, the sensory criteria evaluated indicated that the dates ice cream was well accepted by respondents positively. Due the study, Dates Ice Cream will be able to convince the consumer to adopt this new product innovation.